2020
DOI: 10.3389/fpsyg.2020.00529
|View full text |Cite
|
Sign up to set email alerts
|

A Finger-Based Numerical Training Failed to Improve Arithmetic Skills in Kindergarten Children Beyond Effects of an Active Non-numerical Control Training

Abstract: It is widely accepted that finger and number representations are associated: many correlations (including longitudinal ones) between finger gnosis/counting and numerical/arithmetical abilities have been reported. However, such correlations do not necessarily imply causal influence of early finger-number training; even in longitudinal designs, mediating variables may be underlying such correlations. Therefore, we investigated whether there may be a causal relation by means of an extensive experimental intervent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 100 publications
0
7
1
Order By: Relevance
“…Our results raise questions for Schild et al (2020), who, following 50 training sessions over 10 weeks, found no advantages for finger arithmetic as compared to mainstream arithmetic training. In contrast, students participating in 15-20 sessions of the Botetano Method exhibit impressive results.…”
Section: Discussioncontrasting
confidence: 53%
“…Our results raise questions for Schild et al (2020), who, following 50 training sessions over 10 weeks, found no advantages for finger arithmetic as compared to mainstream arithmetic training. In contrast, students participating in 15-20 sessions of the Botetano Method exhibit impressive results.…”
Section: Discussioncontrasting
confidence: 53%
“…A longitudinal study has shown that the frequency of finger use nevertheless slowed down over timefor boys more than for girlsand was beneficial to calculation mainly during kindergarten, except in low-income children whose accuracy continued to increase with finger use till the second grade (Jordan et al, 2008). This finding, together with mixed results from training studies (Fischer, 2010;Gracia-Bafalluy & Noël, 2008;Ollivier et al, 2020;Schild et al, 2020), suggests that finger use assists mental calculation only during a limited period of time that varies with individual learning opportunities. However, other studies have revealed that finger counting experience remains imprinted in number representation throughout development and beyond.…”
Section: Cognitive and Neural Signatures Of Finger Countingmentioning
confidence: 99%
“…Here, we only focus on the conduction and the results of the two linguistic trainings. For detailed information about the numerical control training, the content of the control training and and its results, see Schild et al (2020).…”
Section: Training Studymentioning
confidence: 99%
“…Length and organization of the training for the non-linguistic control training was comparable to that of the two language groups. For more information about the training material of the control training, see Schild et al (2020).…”
Section: Training Materialsmentioning
confidence: 99%
See 1 more Smart Citation